2010
DOI: 10.1097/nmd.0b013e3181cc532d
|View full text |Cite
|
Sign up to set email alerts
|

Expressed Emotion and Health Outcomes Among Mexican-Americans With Schizophrenia and Their Caregiving Relatives

Abstract: Past studies have demonstrated a clear relationship between expressed emotion (EE) and relapse for individuals with schizophrenia. However, little attention has been directed toward exploring whether EE may have negative health consequences for caregivers as well. We recruited 60 Mexican-American family caregivers of individuals with schizophrenia and examined whether EE predicted the health of caregivers and ill relatives approximately 13 months later. For caregiving relatives, the EE indices of emotional ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…There have been many studies on both the relationship between EE and depression in patients (Hayhurst, Cooper, Paykel, Vearnals, & Ramana, 1997;Hinrichsen, Adelstein & Mcmeniman, 2004;Silk et al, 2009) and the association between EE and the caregivers' health among patients with schizophrenia (Breitborde et al, 2009;Breitborde, L opez, & Kopelowicz, 2010). A number of studies have also found that EE in caregivers of dementia patients was related to caregivers' strain and distress (Bledin, MacCarthy, Kuipers, & Woods, 1990), burden (Nomura et al, 2005;Vitaliano, Russo, Young, Teri, & Maiuro, 1991), and psychological well-being (Gilhooly & Whittick, 1989).…”
Section: Introductionmentioning
confidence: 96%
“…There have been many studies on both the relationship between EE and depression in patients (Hayhurst, Cooper, Paykel, Vearnals, & Ramana, 1997;Hinrichsen, Adelstein & Mcmeniman, 2004;Silk et al, 2009) and the association between EE and the caregivers' health among patients with schizophrenia (Breitborde et al, 2009;Breitborde, L opez, & Kopelowicz, 2010). A number of studies have also found that EE in caregivers of dementia patients was related to caregivers' strain and distress (Bledin, MacCarthy, Kuipers, & Woods, 1990), burden (Nomura et al, 2005;Vitaliano, Russo, Young, Teri, & Maiuro, 1991), and psychological well-being (Gilhooly & Whittick, 1989).…”
Section: Introductionmentioning
confidence: 96%
“…Meanwhile, the burden of the caring role has been shown to significantly deplete family social networks, an important buffer for stress [16]. Although less is known about the physical health correlates of caring for a relative with psychosis, there is evidence that the style of caring and severity of psychotic symptoms increases the risk of physical health problems for relatives [17, 18]. Findings from investigations of Alzheimer’s disease provide a basis for further hypotheses – studies have suggested that stress is associated with weakening of carers’ immune functioning and accelerated ageing [19].…”
Section: Introductionmentioning
confidence: 99%
“…While expressed emotion, or expressions of over-involvement (“smothering”), criticism or hostility vary from individual to individual; these expressions also vary cross-culturally (41). Moreover, the phenomenon of familial expressed emotion predicts different outcomes depending on the ethnicity of individuals; higher expressed emotion has been linked with poorer outcomes in non-Hispanic whites but not in Hispanic individuals in schizophrenia treatment (4243). At present, there is a dearth of literature on minority couples in treatment.…”
Section: Discussionmentioning
confidence: 99%